2023
DOI: 10.1186/s12891-023-06464-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy for patients with hip and knee osteoarthritis in Germany: a survey of current practice

Abstract: Background Osteoarthritis (OA) of the hip and the knee is common and leads to pain, stiffness and disability. Clinical practice guidelines (CPG) provide recommendations to assist healthcare professionals in clinical decision-making. Although evidence-based physiotherapy has been shown to be effective in the management OA, a gap between clinical practice and guideline recommendations exists. Little is known about OA management provided by physiotherapists in Germany and whether treatment aligns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…At worst, the probability of conservative treatment success is reduced, symptom and impairment duration are prolonged, and interventional care (imaging, injections, surgery) may become more likely (ref). Findings show similarity to the results of the studies of physiotherapeutic management of nonspeci c low back pain and hip and knee osteoarthritis in Germany (17,41).…”
Section: Adjunctive Treatmentsupporting
confidence: 80%
See 1 more Smart Citation
“…At worst, the probability of conservative treatment success is reduced, symptom and impairment duration are prolonged, and interventional care (imaging, injections, surgery) may become more likely (ref). Findings show similarity to the results of the studies of physiotherapeutic management of nonspeci c low back pain and hip and knee osteoarthritis in Germany (17,41).…”
Section: Adjunctive Treatmentsupporting
confidence: 80%
“…Both studies found evidence of the high use of passive treatment strategies, such as massage, kinesio-taping, or manual therapy, which are not recommended by clinical practice guidelines for the respective patient group (17,41). Given that there is a signi cant risk of low value care being recommended more often in non-academically trained physiotherapists, differences in therapist education may be signi cantly impacting patient care.…”
Section: Adjunctive Treatmentmentioning
confidence: 99%
“…In December 2021, the survey among German physiotherapists was completed, and results on the management of patients with hip and knee osteoarthritis and guideline adherence were published [50] (part 1 of the research project). Ethics approval for the second part of the research project was obtained in August 2022, and the semistructured interviews were conducted between January and September 2023.…”
Section: Resultsmentioning
confidence: 99%
“…Как показывает наша практика и исследования, проводимые специалистами разных стран, в настоящее время сохраняются проблемы диагностики, маршрутизации, качества лечения пациента с ОА на амбулаторном приеме [20]. Соответственно, можно говорить о том, что КЖ пациентов с ОА остается не на самом высоком уровне в силу различных причин, в частности отсутствия немедикаментозных методов терапии или ограничения их перечня исключительно физиотерапевтическими процедурами, нарушения алгоритмов помощи пациентам с ОА (рассмотрены в 2014 г. на Всемирном конгрессе по остеопо розу, остеоартриту и мышечно-скелетным заболеваниям, Се вилья (Испания) (World Congress on Osteoporosis, Osteoarthritis and Musculoskeletal Diseases -WCO-IOF-ESCEO), постоянно корректируются в современных клинических рекомендациях) [14,21,22].…”
Section: Discussionunclassified